CRISPR Gene Editing in Strawberry - Seonghee Lee; Cheolmin Yoo; Kevin M. Folta; Vance Whitaker (EDIS, 2018)
Because cultivated strawberries are genetically complex, conventional breeding of strawberry can be difficult. Therefore, gene editing can be useful when developing strawberry varieties. This 3-page document discusses CRISPR gene editing in strawberry. Written by Seonghee Lee, Cheolmin Yoo, Kevin Folta, and Vance M. Whitaker and published by the UF/IFAS Horticultural Sciences Department, February 2018. http://edis.ifas.ufl.edu/hs1315